The systematic review of the international models of athlete development pathway - Kinugasa, T.; Morley, E.; Funasaki, K.; Fujiwara, A.; Gulbin, J. (Journal of High Performance Sport, 2019)
The development of an athlete from their commencement in sport at the local level to achieving the serial medallist status at the international level can be a long and winding pathway. From a theoretical point of view, various international models and frameworks of sport and athlete development are available, but sporting stakeholders especially National Sport Federations are `wondering` which models or frameworks to adopt at the practical level. After the literature review, there are various models of athlete development pathway, but the international framework, FTEM (Foundation, Talent, Elite, and Mastery), is a useful inclusive framework for understanding the stages of athlete development from grassroots to the podium with practical application by National Sport Federations. The national framework is required to the whole of sport for bridging the gap between theory and practice by taking into account the cultural and social context in Japan.